Kajian Strategi Branding UMKM Quiinz Bowl Bojongsoang sebagai Adaptasi Pasca Pandemic: Studi kasus UMKM Quiinz Bowl - Prahara, Gema Ari (Universitas Komputer Indonesia, 2023)
The development of the post-pandemic culinary business has experienced various problems, especially for micro businesses. Problems exist in internal and external elements. In general, there is growth in the culinary sector on a local and regional scale. This problem is experienced by MSMEs Quiinz Bowl, a home-based business that continues to survive and continue to do business in the midst of a changing market. The Quiinz Bowl is trying to try to get out of the post-pandemic barrier. Even though demand is declining, this business is still looking for a way out that can maintain the existence of its micro business. The Quiinz Bowl uses a branding strategy in determining the way forward. This study uses qualitative methods with recommendations for branding strategy analysis implemented in concrete steps in visual communication media Branding strategy with the rejuvenation of previous visual characters is a step to trigger novelty. The use of instore media, is a solution used as an early stage of strengthening Quiinz Bowl products.